POTENTIAL DEVELOPMENT OF PROBLEM-ORIENTED PROJECT-BASED LEARNING MODEL IN MANUFACTURING PRODUCT DESIGN COURSE IN VOCATIONAL HIGHER EDUCATION - Mudriadi, Windi; Yahya, Muhammad; Supriadi, Supriadi (Pascasarjana Universitas Negeri Makassar, 2025)
This study conducted a needs analysis to explore the potential for developing a learning model adapted from the problem-oriented project-based learning (POPBL) approach for the Manufacturing Product Design course. The analysis incorporated observations of learning activities, student needs and interest assessments, and lecturer requirements. Findings indicated a student interest score of 82.71%, signifying high enthusiasm for a problem-solving-oriented model themed around Appropriate Technology-based Manufacturing Product Design. However, student comprehension of mechanical design concepts scored 65.42%, suggesting areas for improvement. Lecturers acknowledged the model's relevance but emphasized the need for guidance on implementing effective learning tools and methods. Consequently, a new model was proposed to enhance students' competencies in producing appropriate technology-based manufacturing products. This model prioritizes active student engagement and logical understanding through a structured process including need identification, technical specification preparation, concept design, decision-making, and documentation. Lecturers serve as facilitators, guiding students to identify problems and develop solutions while adhering to technical and safety standards. The proposed model's management considers five components: syntax, social systems, reaction principles, support systems, and instructional impacts, aiming to improve learning outcomes in mechanical design.